The settlement dispute of Venezuela's referendum on Guyana's indigenous communities' territorial concerns by ICJ - Gunawan, Yordan; Syamsudin, Wa Ode Fithrah Az-zalia; Budiman, Arif (Jurnal Hukum Novelty, 2024)
Introduction to The Problem: Venezuela held a referendum on December 3, 2023, within its own borders, to address territorial matters with the indigenous communities of Guyana. The referendum was conducted in accordance with the indigenous Pemon community's desire, originating from the Essequibo area of Guyana. Guyana asked the International Court of Justice (ICJ) to block the act of Venezuela, but the voters rejected the ICJ and continued doing the referendum. Purpose/Objective Study: This study aims to examine the settlement dispute, especially between Venezuela and Guyana, through the International Court of Justice (ICJ). Does the ICJ have jurisdiction over the territorial dispute between Venezuela and Guyana, particularly concerning the potential impact of the Venezuela referendum on the land rights and self-determination of indigenous peoples of Guyana? How did the ICJ handle the dispute from the Venezuela referendum, and what legal principles and precedents were used in resolving the territorial dispute? Design/Methodology/Approach: This research adopts a socio-legal approach to analyze the dispute resulting from the Venezuelan referendum regarding the territorial issues of the Indigenous Community of Guyana. Findings: The ICJ thoroughly examined the legality of the 1899 arbitration decision, carefully assessed the established territorial boundaries, and considered the potential harm to the rights and interests of the Guyanese people. These findings underscore the complex interplay between legal principles and practical challenges, highlighting the need for cooperation and diplomacy in effective international dispute resolution. The ICJ holds jurisdiction over the longstanding territorial conflict between Venezuela and Guyana as outlined in the 1966 Geneva Agreement and reinforced by the December 2020 resolution. The court's recent decision to delay Venezuela's planned referendum reflects its recognition of the potential consequences that unilateral actions might have on the land rights and self-determination of Guyana's indigenous communities, emphasizing the court's commitment to balanced and careful adjudication. Paper Type: Research Article